Note on Composition of Origanum vulgare Seed Cake - Karnik, M. G.; Sharma, O. P. (Indian Forester, 1968)
The seed cake left after the extraction ef oil from Origanum vulgare seeds has been analysed. The cake is found to be rich in Nitrogen content and is reported to be suitable as a fertilizer.